METHODS OF APPLICATION OF COMPUTER VISION IN MEDICINE - Yakubova Dilrabokhon Davlatboyevna (Bright Mind Publishing, 2025)
This article briefly discusses the ancient traditions, values, and the rich cultural heritage of the Uzbek people, which has a long and significant history.
Keywords: literature and art, craftsmanship, architecture, historical sources, national clothing, traditions, monuments.